A family of unconventional deubiquitinases with modular chain specificity determinants - Thomas Hermanns (Nature Portfolio, 2018)
Deubiquitinating enzymes (DUBs) are essential to modulate ubiquitin signaling. While known DUBs can be grouped into six families, the authors here present biochemical and structural evidence for a seventh DUB family, defining determinants of substrate specificity for two representative enzymes.